The influence of the NRG1/ERBB4 signaling pathway on pulmonary artery endothelial cells - Jin‐Bo Huang; Qin Shen; Zhi‐Qi Wang; Song‐Shi Ni; Fei Sun; Yun Hua; Jian‐An Huang (Pulmonary Circulation)
Abstract This study aimed to examine the influence of the Neuregulin‐1 (NRG1)/ERBB4 signaling pathway on the function of human pulmonary artery endothelial cells (HPAECs) and investigate the underlying mechanisms. Enzyme‐linked immunosorbent assay indicated that ERBB4 levels in the serum of patients with pulmonary embolism (PE) were significantly higher than those of healthy controls (p < 0.05). In cellular studies, thrombin stimulation for 6 h led to a significant decrease in cell viability and overexpression of ERBB4 compared to control (p < 0.05). In the NRG1 group, apoptosis of HPAECs was reduced (p < 0.05), accompanied by a decrease in ERBB4 expression and an increase in p‐ERBB4, phosphorylated serine/threonine kinase proteins (Akt) (p‐Akt), and p‐phosphoinositide 3‐kinase (PI3K) expression (p < 0.05). In the AG1478 group, there was a significant increase in HPAEC apoptosis and a significant decrease in p‐ERBB4 and ERBB4 expression compared to the Con group (p < 0.05). In the AG1478 + NRG1 group, there was an increase in the apoptosis rate and a significant decrease in the expression of p‐ERBB4, ERBB4, p‐Akt, and phosphorylated PI3K compared to the NRG1 group (p < 0.05). In animal studies, the PE group showed an increase in the expression of ERBB4 and p‐ERBB4 compared to the Con group (p < 0.05). NRG1 treatment led to a significant reduction in embolism severity with decreased ERBB4 expression and increased p‐ERBB4 expression (p < 0.05). Gene set enrichment analysis identified five pathways that were significantly associated with high ERBB4 expression, including CHOLESTEROL HOMEOSTASIS, OXIDATIVE PHOSPHORYLATION, and FATTY ACID METABOLISM (p < 0.05). Therefore, NRG1 inhibits apoptosis of HPAECs, accompanied by a decrease in ERBB4 and an increase in p‐ERBB4. NRG1 inhibition in HPAECs apoptosis can be partially reversed by inhibiting ERBB4 expression with AG1478. ERBB4 has the potential to be a novel biological marker of PE.